Alcohol Use among High School Learners in the Peri-Urban Areas, South Africa: A Descriptive Study on Accessibility, Motivations and Effects - Mmampedi Mathibe; Lindiwe Cele; Perpetua Modjadji (MDPI AG, 2022)
Learners are vulnerable to alcohol use and its negative effects, largely due to accessibility of alcohol products, especially in the localities with poor socioeconomic status and infrastructure. This study aimed to determine the accessibility, motivations and effects of alcohol use among high school learners (n = 403) in Tshwane North and West, South Africa, using a descriptive, cross-sectional design. Data were collected using a validated questionnaire and analysed using STATA 17. Learners (16 ± 2 years) had poor demographic status and lifestyle behaviors. Availability of alcohol outlets (54%) near schools was reported, and learners indicated easy access (65%) to taverns and bottle stores (30%), and purchasing alcohol without a proof of identity document (70%). Motivations for alcohol use were self-pleasure (36%), coping with stress (24%) and increasing self-esteem (19%). Almost half of the learners (49%) introduced themselves to alcohol use, while others were influenced by friends (36%) and family (14%). Reported alcohol related effects were a negative impact on health (56%), brain function (25%) and school work (12%), in addition to social harms, including problems with friends (25%) and parents (17%), physical fights (19%) and engaging in risky sexual behaviour (11%). Effective strategies are necessary to address underage alcohol use and should include regulating the proximity of alcohol outlets to schools, life skills training to address learners' drinking motives and constantly alerting parents about the relevance of modeling behaviour.